2014
DOI: 10.5539/ies.v7n13p261
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Well Being: First-Year Student Experience in University

Abstract: The current study explored first-year student experience in receiving social support and its relation to their ability to adapt with university ethos. It also explored how social support on academic adjustment, social adjustment and emotional adjustment among students were significantly associated with student well-being. This qualitative research utilized individual semi-structured interview protocols to gather narrative data from 16 university students. All students were interviewed twice in order to see cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 29 publications
(27 reference statements)
6
83
0
10
Order By: Relevance
“…Similarly, a non-experimental study found that support from family, friends and significant others were associated with positive psychological strengths and subjective well-being among engineering students (Khan & Husan, 2010). Another qualitative study in Malaysia highlighted the importance of social support on first-year students' well-being (Awang, Kutty, & Ahmad, 2014). Social interactions within (peer, senior and school support) and outside (family and sibling support) academic environments were of great importance on students' academic, social and emotional adjustment (Awang et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, a non-experimental study found that support from family, friends and significant others were associated with positive psychological strengths and subjective well-being among engineering students (Khan & Husan, 2010). Another qualitative study in Malaysia highlighted the importance of social support on first-year students' well-being (Awang, Kutty, & Ahmad, 2014). Social interactions within (peer, senior and school support) and outside (family and sibling support) academic environments were of great importance on students' academic, social and emotional adjustment (Awang et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Another qualitative study in Malaysia highlighted the importance of social support on first-year students' well-being (Awang, Kutty, & Ahmad, 2014). Social interactions within (peer, senior and school support) and outside (family and sibling support) academic environments were of great importance on students' academic, social and emotional adjustment (Awang et al, 2014). Similarly, in New Zealand there is evidence that highlights the importance of both peer and family support (Benseman, Coxon, Anderson, & Anae, 2006;Glaser, Hall, & Halperin, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been shown to promote mental health and acts as a buffer against stressful life events (Dollete & Phillips, 2004). Social support is derived from a network of people drawn from family, friends and community (Awang, Kutty, & Ahmad, 2014;Zimet, Dahlem, Zimet, & Farley, 1988). A lack of social support is a determinant of mental health problems including depressive symptoms among university students (Bukhari & Afzal, 2017;Safree & Dzulkifli, 2010), and has a negative impact on quality of life for students (Dafaalla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it was found that the impact of academic stress defined as frustrations, conflicts, pressures, changes and self-imposition on psychological wellbeing depends on the level of perceived social support from friends (Glozah, 2013). A study found that social support from family and friends has a substantial impact on the emotional, social and academic performance of university students (Awang et al, 2014). However, in this developmental stage of adolescence, friends are increasingly more important as a source of social support compared to family (Kugbey, 2015), as the emphasis shifts from parents to that of peers as the child seeks to individuate from family.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, little has been done on student engagement at higher education institutions (HEIs) in Malaysia. Although several studies have been conducted, they are based on small scale projects and individual universities (Abdullah et al, 2010;Awang et al, 2014, Kasim et al, 2012Yusoff, 2013).…”
Section: Introductionmentioning
confidence: 99%